Some properties of extracellular protease from Bacillus licheniformis LBBL-11 isolated from “iru”, a traditionally fermented African locust bean condiment (International Journal of Medicine and Medical Sciences, 2020)
Twelve strains of Bacillus licheniformis isolated from traditionally fermented African locust bean (iru) were evaluated in respect to production of protease on skim milk agar. B. licheniformis LBBL-11 exhibited the highest proteolytic activity with a diameter of clear zone measuring 35.0 mm. Production of protease from B. licheniformis LBBL-11 was further studied by growing the strain on nutrient broth. Maximum protease production was 18.4 U/ml at 48 hour of growth which coincided with the end of exponential phase. The protease from this Bacillus sp had optimum pH of 8.0 and was stable over a wide pH range of 5.0 - 11.0. The optimum temperature for the protease activity was 60oC. The enzyme was 95% stable at 60oC after 60 min of incubation. These properties indicate possible application of B. licheniformis LBBL-11 as potential starter culture for the fermentation of African locust bean under controlled conditions of temperature and pH.